The determinants of car ownership among working adults in Penang, Malaysia - Lee, Lian Yee; Cheah, Yong Kang (Universiti Utara Malaysia, 2015)
Penang has the third highest rate of car ownership in Malaysia. Traffic congestion issues have worsened alarmingly over the past few years. The objective of the present study was to investigate the factors affecting car ownership in Penang. A logit model and data from a primary survey consisting of 498 respondents were used for an in-depth analysis. The findings of the present study show that age, gender, ethnicity, income, education and parking issues are significant determinants of car ownership. In particular, individuals who are aged between 26 and 35 years; females; Chinese; high income earners and tertiary–educated, are more likely to own cars compared to others. Based on these findings, several intervention strategies are recommended.